What gets measured gets done! Towards an Afro-barometer for tracking progress in achieving Sustainable Development Goal 5. Issue 1 (2nd January 2018) - Nhamo, Godwell; Nhamo, Senia; Nhemachena, Charles
Abstract: What gets measured gets done! This saying implies that without quantifying what needs to be done, doing it may not be possible. This term is relevant to how African countries will implement the United Nations (UN) Sustainable Development Goals (SDGs) by 2030, particularly in tracking progress on SDG 5 on gender equality and the empowerment of women and girls. During the Millennium Development Goals (MDGs), governments failed to establish baselines for measuring progress in meeting the goals. To ensure that no country is left behind, the UN came up with a list of indicators (Tiers 1-3) for tracking progress in achieving SDGs targets. Tier 1 indicators fall in conventional data sets and almost all countries have these data. The process for implementation, through domestication and localisation by countries, includes the responsibilities of reporting, tracking and monitoring. The article highlights the importance of attempts to establish a broad baseline of data on women in Africa. An Afro-barometer, drawing from UN Tier 1 indicators and using a composite index and data drawn from the World Development Indicators (WDI), is a tentative step towards a baseline for tracking progress towards achieving SDG 5 in Africa. The research established data for 52 of the 54 African countries on women for three indicators, namely: women's political representation, maternal mortality rates and women's labour force participation. The gaps in the available data, places a question mark over the capacity and will to measure key indicators of gender inequality by countries. Implementation and reporting is integral to the achievement of the SDGs as well as the African Agenda 2063 and call for political will and resources on the continent to move from the merely aspirational, towards the transformation that the agendas propose.